Interactions of stimulus quality and frequency on N400 in Chinese character recognition: Evidence for cascaded processing. (10th January 2020) - Zhang, Yong; Zhou, Meiling; Wang, Quanhong
Highlights: Stimulus blurriness interacted with character frequency on the response times. Stimulus blurriness interacted with character frequency on the N400 amplitude. Pre-lexical processing of Chinese characters can be cascaded to semantic stage. The blurriness-by-frequency interaction on the RTs and N400 fits with IA model. Abstract: Event-related brain potentials (ERPs) were recorded during a delayed character-matching (target-probe matching) task to examine the joint effects of stimulus quality (blurriness) and character frequency on the N400. The behavioral results indicated robust interactive effects of stimulus quality and character frequency on response times, suggesting the cascade of pre-lexical activation to the lexical stage. The ERP results showed an interaction between stimulus quality and character frequency on N400-like amplitude. As the N400 is basically a marker of semantic processing, these ERP findings suggested that the direct impact of stimulus blurriness on pre-lexical processing could be further cascaded to semantic processing via lexical stage. The converging behavioral and N400 evidence for the interactive effects of stimulus quality and character frequency accords well with the interactive activation (IA) model, in which stimulus quality and character frequency affect at least a common stage in a cascaded processing manner.